Perceptions of the Second Sophistic and its times = Regards sur la Seconde Sophistique et son époque - Schmidt, Thomas S.; Fleury, Pascale (Phoenix. Supplementary volume (Toronto, Ont.), 2011)
From a workshop held at Université Laval, Perceptions of the Second Sophistic and its Times brings together fourteen essays and a range of perspectives, including work from scholars in literature, philology, linguistics, history, political science, sociology, and religion. The essays explore the Second Sophistic and describe how the intellectual elites of this period perceived and defined themselves, how they were judged by later authors, and how we understand them today."--Pub. desc.